Proceedings of the 2019 CHI Conference on Human Factors in Computing Systems 2019
DOI: 10.1145/3290605.3300919
|View full text |Cite
|
Sign up to set email alerts
|

Estimating Touch Force with Barometric Pressure Sensors

Abstract: Finger pressure offers a new dimension for touch interaction, where input is defined by its spatial position and orthogonal force. However, the limited availability and complexity of integrated force-sensing hardware in mobile devices is a barrier to exploring this design space. This paper presents a synthesis of two features in recent mobile devices-a barometric sensor (pressure altimeter) and ingress protectionto sense a user's touch force. When a user applies force to a device's display, it flexes inward an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
10
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 10 publications
(10 citation statements)
references
References 29 publications
0
10
0
Order By: Relevance
“…Detecting taps. Quinn [7] recently showed that, in devices with ingress protection, forces on touchscreen can be detected using the device's internal barometer. To this end, a robotic arm was programmed to perform five second touch contacts with three different force levels (1, 3, and 5N).…”
Section: B Accuracy Resultsmentioning
confidence: 99%
See 4 more Smart Citations
“…Detecting taps. Quinn [7] recently showed that, in devices with ingress protection, forces on touchscreen can be detected using the device's internal barometer. To this end, a robotic arm was programmed to perform five second touch contacts with three different force levels (1, 3, and 5N).…”
Section: B Accuracy Resultsmentioning
confidence: 99%
“…Unlike the 5-second robotic arm touch contacts in [7], finger taps have a short touchscreen contact time. In our experiment, the touchscreen contact time of a finger tap ranged from 24ms to 183ms, with the average of 85ms.…”
Section: B Accuracy Resultsmentioning
confidence: 99%
See 3 more Smart Citations